2021
DOI: 10.1038/s41598-021-82888-9
|View full text |Cite
|
Sign up to set email alerts
|

bFGF and collagen matrix hydrogel attenuates burn wound inflammation through activation of ERK and TRK pathway

Abstract: Burn injuries are most challenging to manage since it causes loss of the integrity of large portions of the skin leading to major disability or even death. Over the years, hydrogels are considered as a significant delivery system for wound treatment because of several advantages over other conventional formulations. We hypothesized that the bFGF-collagen-AgSD incorporated hydrogel formulation can accelerate the rate of burn healing in animal model and would promote fibroblast cell proliferation. Neovasculariza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…CSL optical collagen densities were substantially higher than those of the CA/SA group (p < 0.05, n = 3). Besides, in this study showed that the collagen in CSL group arranged regularly, and the new epidermis was much closer in appearance to that of normal skin, which indicated that CSL can accelerate re-epithelization and wound repairing [57]. These results were consistent with those of the in vitro experiments, indicating that LAP could help to enhance wound healing through promoting cell proliferation, migration, and collagen secretion.…”
Section: Histological Evaluationsupporting
confidence: 87%
“…CSL optical collagen densities were substantially higher than those of the CA/SA group (p < 0.05, n = 3). Besides, in this study showed that the collagen in CSL group arranged regularly, and the new epidermis was much closer in appearance to that of normal skin, which indicated that CSL can accelerate re-epithelization and wound repairing [57]. These results were consistent with those of the in vitro experiments, indicating that LAP could help to enhance wound healing through promoting cell proliferation, migration, and collagen secretion.…”
Section: Histological Evaluationsupporting
confidence: 87%
“…Also, collagen hydrogels provided a prolonged antibacterial activity when they involved simvastatin, and findings revealed that these materials could stimulate macrophages which is useful in wound healing processes [26]. e MTT assay of Chakrabarti et al study showed that bFGF and collagen matrix hydrogel had minimal toxicity on the L929 mouse fibroblast cell line, did not inhibit cell proliferation, and could be further investigated in burn wounds [27]. In the present study, the antibacterial evaluations showed that the number reduction of E. coli was more than S. aureus.…”
Section: Discussionmentioning
confidence: 99%
“…bFGF stimulated migration of fibroblasts and synthesis of collagen, as well as promoted angiogenesis. It also promoted wound healing by pathways for nerve growth factor (NGF), tropomyosin-receptor kinase A (TrkA), p-TrkA, extracellular regulated kinase 1 and 2 (ERK1/2), p-ERK1/2, NF-kβ, and p-NF-kβ [ 55 ].…”
Section: Promotion Of Wound Healingmentioning
confidence: 99%